Ni–MoS2 composite coatings as efficient hydrogen evolution reaction catalysts in alkaline solution. (20th April 2017) - Yin, Xucai; Dong, Haifeng; Sun, Gang; Yang, Wu; Song, Ailing; Du, Qinghua; Su, Li; Shao, Guangjie
Abstract: It remains an important project for the development of water splitting electrolyze to design and synthesis of more efficient non-noble metal catalyst. In this work, a structured Ni–MoS2 composite coating has been synthesized under supergravity fields with nickel sulphamate bath containing suspended MoS2 submicro-flakes. X-ray diffraction patterns indicate that the MoS2 submicro-flakes have been successfully incorporated into the Ni matrix. Additionally, SEM shows that the prepared Ni–MoS2 composite coatings display finer grain size than the pure Ni coatings, which can increase the electrochemistry surface area and the active site of hydrogen evolution reaction. Therefore, due to the synergistic effect of molybdenum disulfide and nickel, the Ni–MoS2 composite coatings are directly used as binder-free electrode, which exhibits outstanding electrocatalytic activity for HER in 1.0 M NaOH solution at room temperature. The Ni–MoS2 composite coatings demonstrated an outstanding performance toward the electrocatalytic hydrogen production with low overpotential (100 mA cm −2 at η  = 207 mV), a Tafel slope as small as 65 mV dec −1, and stable cycling performance (1200 cycles). The preeminent HER performance of this catalyst suggests that it may hold great promise for practical applications. Highlights: Ni–MoS2 composite coating is synthesized under supergravity fields. Synergistic effect exists of Ni and MoS2 enhance the catalytic activity of HER. Low overpotential, small Tafel slope, and superior durability are achieved.